If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12n + 3 = 39 Reorder the terms: 3 + 12n = 39 Solving 3 + 12n = 39 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 12n = 39 + -3 Combine like terms: 3 + -3 = 0 0 + 12n = 39 + -3 12n = 39 + -3 Combine like terms: 39 + -3 = 36 12n = 36 Divide each side by '12'. n = 3 Simplifying n = 3
| 2x^3+8=24 | | -2(x+4)=-3x+8 | | -31+18x-17X+9= | | 3(2r+5)-4(r-9)= | | -2(1+x)=7-5x | | b-4=-19 | | -7(-6b-5)=35-5b | | 6(2x-10)=0 | | 14+3d-7=12.10 | | -5(x+6)=5x-20 | | -(8+x)=-8+7x | | -18=18v | | 14x^2+10x-8=0 | | 2(t-4)-3(4t-5)=10-5(7t+3) | | 32+4m=-3(-5m-2)+2m | | -3(n-5)=15+4n | | 6x-2=3x-10 | | 4(1/4+x)=5 | | 7z-4=7z-z | | 6(1+7n)=40+8n | | 2x^2+9x=35 | | -4x^2(5x^2-21x-y)= | | 3(x-1)=-7(x-1) | | 1-5m=6(1-m) | | 7(3x+2)+22=36 | | -0.04x+1.32=1.08 | | 4(6x+5)=2+6x | | -3(4-y)=27 | | -1(3w-4)+12w=3w+4 | | 3m-5=5m+2 | | -27-3k=-6(k+2) | | X+20=6x+5 |